Quantitative Analysis of Luxs Gene Expression and Its Role in Pathogenesis of Proteus mirabilis - Alzubaidy, Fatima Hamza (Medical Science Journal for Advance Research, 2026)
Background: Proteus mirabilis was the most important pathogens that cause infection, these bacteria have many different characteristic lead to become more virulence and pathogenesis such as swarming motility, Biofilm formation lead to antibiotic resistance. The inflammation and tissue necrosis result from ability of bacteria to urease production. Many different type of virulence gene found in P. mirabilis, such as ( Rsb A, Lux S and Ure R).In the current study the identification of P.mirabilis by VITEK-2 Compact system,then detect the correlation between some virulence gene with different type of antibiotic and detect the 16SRNA and Lux S gene by Real time PCR. The conclusion of study displays the ability of Proteus infection result from have many different virulence factors, and the correlation with antibiotic was significant as result showed (nitrofurantoin and trimethoprim) highly significant against (lux s, rsb, ure r), but (ampicillin) gave significant only against (lux s, rsb, ure r).